2018
DOI: 10.1002/lipd.12029
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific Alterations in Serology and the Expression of Liver FATP4 Protein in Offspring Exposed to High‐Fat Diet during Pregnancy and/or Lactation

Abstract: Changes in dietary composition will have a significant impact on the nutritional status of the mother and the offspring. To examine the relevant hormone level changes during lactation and the expression of fatty acid transporters in the placenta and liver under the condition of a high-fat (HF) diet, we established HF animal models and conducted a cross-fostering program to mimic the shift in diet. On gestation day (GD)18, the weight of placenta in the HF group was significantly higher than that in the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The period of maternal diet exposure, characteristics of offspring (sexes and death age), and biochemical measurements of the offspring are presented in Supplementary Table S3 . The HFD exposure ranges from 21 to 154 days [ 23 , 37 , 61 64 , 74 , 88 , 89 ]. In relation to gender, 31 articles verified both genders [ 21 , 35 , 36 , 41 , 50 , 54 , 57 , 58 , 60 – 62 , 64 66 , 68 , 71 , 72 , 80 82 , 84 92 , 94 , 96 , 99 ]; 23 studies analyzed males [ 14 , 18 , 30 33 , 37 , 40 , 42 , 48 , 51 53 , 55 , 56 , 63 , 74 , 75 , 77 , 78 , 83 , 91 , 93 , 100 ], 11 evaluated females [ 23 , 59 , 67 , 70 , 73 , 76 , 79 , 87 , 88 , 95 , 97 ], and only one did no report on the offspring sex [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The period of maternal diet exposure, characteristics of offspring (sexes and death age), and biochemical measurements of the offspring are presented in Supplementary Table S3 . The HFD exposure ranges from 21 to 154 days [ 23 , 37 , 61 64 , 74 , 88 , 89 ]. In relation to gender, 31 articles verified both genders [ 21 , 35 , 36 , 41 , 50 , 54 , 57 , 58 , 60 – 62 , 64 66 , 68 , 71 , 72 , 80 82 , 84 92 , 94 , 96 , 99 ]; 23 studies analyzed males [ 14 , 18 , 30 33 , 37 , 40 , 42 , 48 , 51 53 , 55 , 56 , 63 , 74 , 75 , 77 , 78 , 83 , 91 , 93 , 100 ], 11 evaluated females [ 23 , 59 , 67 , 70 , 73 , 76 , 79 , 87 , 88 , 95 , 97 ], and only one did no report on the offspring sex [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In relation to gender, 31 articles verified both genders [ 21 , 35 , 36 , 41 , 50 , 54 , 57 , 58 , 60 – 62 , 64 66 , 68 , 71 , 72 , 80 82 , 84 92 , 94 , 96 , 99 ]; 23 studies analyzed males [ 14 , 18 , 30 33 , 37 , 40 , 42 , 48 , 51 53 , 55 , 56 , 63 , 74 , 75 , 77 , 78 , 83 , 91 , 93 , 100 ], 11 evaluated females [ 23 , 59 , 67 , 70 , 73 , 76 , 79 , 87 , 88 , 95 , 97 ], and only one did no report on the offspring sex [ 69 ]. The ranged age for the offspring was between one day after birth [ 21 , 30 , 35 , 40 , 50 , 52 , 53 , 55 , 62 , 89 ] and 360 days old [ 71 ]. The observed biochemical parameters were TG, TC, HDL, LDL, ALT, and AST.…”
Section: Resultsmentioning
confidence: 99%
“…Through maternal diet alteration (fat, carbohydrate, proteins and specific fatty acids), artificial rearing, cross-fostering, litter size reduction and direct neonatal diet supplementation, researchers are able to narrow their focus to outcomes that result from exposures solely during the period of lactation in animal models. [24][25][26][27] Mouse models have demonstrated milk composition is altered in the setting of maternal nutrition during lactation and maternal disease. 23,[28][29][30] We performed a recent review looking at these outcomes in depth.…”
Section: Cross-fostering Studiesmentioning
confidence: 99%
“…In lactational high fat diet models offspring had resulting abnormal lipid accumulation in white adipose tissue and liver, adipocyte hypertrophy, insulin resistance and divergent gut microbial diversity levels, all signs of offspring metabolic compromise. 18,[24][25][26]31,32 Monks et al set out to dissect the effects of maternal obesity versus maternal high-fat diet during the lactation period. They found that pups reared by lean dams on a high-fat diet during lactation had the fastest rate of growth with F I G U R E 1 Overview of lactational programming.…”
Section: Cross-fostering Studiesmentioning
confidence: 99%
“…High carbohydrate diets fed to pups by gastrostomy, for example, led to increased adult liver fat (12). Lactational HFD also led to increased liver triglycerides and steatosis in several models (13)(14)(15). Small litters used to model early post-natal overnutrition show increased liver oxidative stress, with microsteatosis followed by insulin resistance (16,17).…”
Section: Introductionmentioning
confidence: 99%